Photoreceptor-derived activin promotes dendritic termination and restricts the receptive fields of first-order interneurons in Drosophila. - Ting, C.Y.; McQueen, P.G.; Pandya, N.; Lin, T.Y.; Yang, M.; Reddy, O.V.; O'Connor, M.B.; McAuliffe, M.; Lee, C.H. (Neuron, 2014)
How neurons form appropriately sized dendritic fields to encounter their presynaptic partners is poorly understood. The Drosophila medulla is organized in layers and columns and innervated by medulla neuron dendrites and photoreceptor axons. Here, we show that three types of medulla projection (Tm) neurons extend their dendrites in stereotyped directions and to distinct layers within a single column for processing retinotopic information. In contrast, the Dm8 amacrine neurons form a wide dendritic field to receive ?16 R7 photoreceptor inputs. R7- and R8-derived Activin selectively restricts the dendritic fields of their respective postsynaptic partners, Dm8 and Tm20, to the size appropriate for their functions. Canonical Activin signaling promotes dendritic termination without affecting dendritic routing direction or layer. Tm20 neurons lacking Activin signaling expanded their dendritic fields and aberrantly synapsed with neighboring photoreceptors. We suggest that afferent-derived Activin regulates the dendritic field size of their postsynaptic partners to ensure appropriate synaptic partnership.